2015
DOI: 10.1097/gme.0000000000000276
|View full text |Cite
|
Sign up to set email alerts
|

Extended maternal age at birth of last child and women’s longevity in the Long Life Family Study

Abstract: Objective This study investigated the association between maternal ages at birth of last child and the likelihood of survival to advanced ages. Methods A nested case-control study using Long Life Family Study (LLFS) data. Three hundred and eleven women who survived past the oldest 5th percentile of survival according to birth cohort matched life tables were identified as cases and 151 women who died at ages younger than the top 5th percentile of survival were identified as controls. A Bayesian mixed-effect l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 30 publications
1
45
0
1
Order By: Relevance
“…This is both interesting and important because the ability to conceal older age may suggest a youthfulness that is not just skin deep. In fact, there are several lines of evidence linking youthfulness and longevity to fertility [1, 9092]. Research on centenarians has demonstrated that women who have their last child after the age of 33 had twice the odds of living to age 95 than women who had their last child by age 30 or younger [90].…”
Section: Unique Features Of Age-based Hcstmentioning
confidence: 99%
See 1 more Smart Citation
“…This is both interesting and important because the ability to conceal older age may suggest a youthfulness that is not just skin deep. In fact, there are several lines of evidence linking youthfulness and longevity to fertility [1, 9092]. Research on centenarians has demonstrated that women who have their last child after the age of 33 had twice the odds of living to age 95 than women who had their last child by age 30 or younger [90].…”
Section: Unique Features Of Age-based Hcstmentioning
confidence: 99%
“…In fact, there are several lines of evidence linking youthfulness and longevity to fertility [1, 9092]. Research on centenarians has demonstrated that women who have their last child after the age of 33 had twice the odds of living to age 95 than women who had their last child by age 30 or younger [90]. Patterns such as these are likely, at least in part, attributable to increased likelihood of delayed childbearing among more affluent women, who also have longer life expectancies because they are more affluent (i.e., the SES-health gradient).…”
Section: Unique Features Of Age-based Hcstmentioning
confidence: 99%
“…Notably, haplogroup J has been shown to be also overrepresented in healthy individuals with extreme longevity, including healthy centenarians [61,62]. The latter may give some clue as to a potential cause of another phenomenon, namely, the fact that increased age of birth of last child may be associated with increased female longevity [63,64]. The authors of the latter two Reproductive outcomes and individual repair capacity studies specifically point out that the relationship seen between late childbirth and longevity may simply be an expression of generally slower ageing pattern.…”
Section: Role Of Individual Repair Capacity In Oogenesis and Oocyte Mmentioning
confidence: 99%
“…Lebensjahr bekommen [25]. Tierversuche aktueller Studien zeigen, dass Bluttransfusionen von jüngeren auf ältere Mäuse sowie eine Schwangerschaft einen potenziellen Verjüngungseffekt bei älteren Individuen haben.…”
unclassified